THE ASSOCIATION BETWEEN INDIVIDUAL, PHYSICAL, AND PSYCHOSOCIAL RISK FACTORS AND OCCUPATIONAL FATIGUE AMONG COMMUTER LINE TRAIN WORKERS - Ulfha Aulia Nasution; Baiduri Widanarko (The Indonesian Journal of Public Health, 2023)
Introduction: Occupational fatigue affects workers in various industries including transportation. Commuter train drivers and office workers are subjected to high levels of physical and psychosocial stress, which can lead to occupational fatigue. Aims: to examine the relationship between individual, physical, and psychosocial risk factors and occupational fatigue in commuter train workers in Jakarta, Bogor, Tangerang, and Bekasi. Methods: Individual (i.e., age, gender, marital status, type of work, duration of work, and smoking status), psychosocial (i.e., effort, reward, overcommitment, monotonous work, social support, job satisfaction, and work stress) factors, and occupational fatigue were investigated in 78 commuter line train workers (both drivers and officers). Observing workers' activities yielded physical factors (awkward posture, repetitive work, prolonged work, and material manual handling activities). The association between each risk factor and occupational fatigue was investigated using a logistic regression model. Results: Commuter line officers (OR 4.96, 95% CI 1.77 – 13.85), those with high overcommitment (OR 3.16, 95% CI 1.25 – 8.00), and those with high work stress (OR 1.54, 95% CI 1.19 – 2.00) were more likely to report occupational fatigue than train drivers, who reported low overcommitment and low work stress, respectively. When compared to those who reported low job satisfaction, those who reported high job satisfaction were less likely to report occupational fatigue (OR 0.19, 95% CI 0.07 – 0.52). Conclusion: Job position, overcommitment, and work stress were associated with occupational fatigue.